2013
DOI: 10.1177/0898264313484059
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Service Use Among Depressed, Low-Income Homebound Middle-Aged and Older Adults

Abstract: Objectives This study examined previous mental health service use among low-income homebound middle-aged and older adults who participated in a study testing the feasibility and efficacy of telehealth problem-solving therapy for depression. Method The sample consisted of 188 homebound adults aged 50 years or older. Data on mental health service use were collected at baseline. We used multivariable logistic regression analysis to examine correlates of different types of outpatient service use within the prece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Given the important role of psychosocial factors in both chronic pain and depression, psychosocial interventions, along with pharmacotherapy, are needed. However, lowincome homebound older adults face significant personal and systemic (e.g., availability, accessibility, and affordability) barriers to psychosocial interventions and are more likely to rely on pharmacotherapy for pain, depression, and anxiety (Choi, Kunik, & Wilson, 2013).…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 99%
“…Given the important role of psychosocial factors in both chronic pain and depression, psychosocial interventions, along with pharmacotherapy, are needed. However, lowincome homebound older adults face significant personal and systemic (e.g., availability, accessibility, and affordability) barriers to psychosocial interventions and are more likely to rely on pharmacotherapy for pain, depression, and anxiety (Choi, Kunik, & Wilson, 2013).…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 99%
“…[4] The majority of elderly living with depression experience depressed moods and pessimism, do not have personal hobbies, and do not go outside due to fear of contracting disease, which results in reduced social interactions, loss of mental orientation, increased feelings of loss and loneliness, and a greater incidence of bedridden elderly. [5,6] With the increase of the elderly population, the incidence of elderly housebound, bedridden elderly, and elderly with dementia will continue to increase, which not only threatens health in the elderly but also poses a heavy burden for families and the society. [2]…”
Section: Introductionmentioning
confidence: 99%
“…They found that nearly 1 in 10 older adults in senior centers (9.8%) suffers from clinically significant depressive symptoms 31 as measured by the 9-item Patient Health Questionnaire (PHQ-9) 32 . Providers in the National Aging Network, an array of agencies and programs sponsored by the Older Americans Act and headed by the US Administration for Community Living (), face mounting rates of depression among NYC’s older adults 33 - 35 and are increasingly aware of the biological and psychosocial costs of depression. Depression in later life is associated with declines in cognition and medical status, 36 increased disability, 37 greater risk of falling, 38 and increased risk of suicide 39 as well as nonsuicide mortality 40 …”
mentioning
confidence: 99%